(untitled) (Jurnal Manajemen Bisnis, 2024)
This article discusses direct influence testing of transformational leadership on employees innovative work behavior and the role of knowledge sharing behavior as a mediating variable. The study encompasses 115 participants from the Semarang City Health Service, and the data analysis was carried out using SEM-PLS with SmartPLS version 3 software. The results indicated a significant effect of TL on IWB and KSB. Another noteworthy finding revealed that KSB had a significant impact on IWB. Moreover, the study identified that TL and IWB can be partially mediated by KSB. The study holds both theoretical and practical implications.